IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB DI SD NEGERI 18 AIR KUMBANG - Suryanti, Irmi; Arafat, Yasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This research was conducted with the aim to implement character education of responsibility and discipline on the students of SD Negeri 18 Air Kumbang. This research uses descriptive qualitative research type. Data analysis used is Miles and Huberman analysis and validated by technique and source triangulation method. After doing research, in the implementation of character education discipline and responsibility in SD Negeri 18 Air Kumbang there are 3 aspects of planning, implementation, and evaluation. The planning is done by entering the character education discipline and responsibility into the curriculum. Integrating the character of discipline and responsibility in a variety of activities one of which is a self-development activities, school culture and subjects in school. Then in the evaluation is done by assessing student attitudes and doing joint evaluation conducted by principals and teachers and parents of students.